Die verhouding tussen Africo Christian en George Schmidt : 1737-1743 (Historia, 2021)
Africo Christian's association with George Schmidt, 1737-1743. In the annals of the Moravian Church Africo (Christian) is only remembered for being one of George Schmidt's Khoikhoi converts. This article attempts to give a more detailed account of his life. In the 1730's he introduced Schmidt, first missionary to South Africa, to the Khoikhoi lifestyle, and is a unique example of how the process of transformation manifested itself in the life of a colonial Khoikhoi. Africo Christian is thus portrayed as the most remarkable Khoikhoi personality known at the Cape between 1737 and 1743 in terms of his adaptability to the socio-economic order of the Cape and his tran~formation from heathen to Christian. Despite the strained relations between missionary and convert, at times, Schmidt had to acknowledge the leadership qualities and social standing of Africo as a clan leader. This seemed to have been an important reason for entrusting the mission station at the time of his departure in October 1743 to Africo Christian.
Keywords: Genadendal; Cape of Good Hope; Christianity; Botha T.; Kibido; Schmidt G.; Moravian mission stations; Khoikhoi; Christian A.; Hartebeestekraal